Synthesis of nucleoside and nucleotide conjugates of bile acids, and polymerase construction of bile acid-functionalized DNA - Ikonen, Satu; Macícková-Cahová, Hana; Pohl, Radek; Sanda, Miloslav; Hocek, Michal (Organic & biomolecular chemistry, 2010)
Aqueous Sonogashira cross-coupling reactions of 5-iodopyrimidine or 7-iodo-7-deazaadenine nucleosides with bile acid-derived terminal acetylenes linked via an ester or amide tether gave the corresponding bile acid-nucleoside conjugates. Analogous reactions of halogenated nucleoside triphosphates gave directly bile acid-modified dNTPs. Enzymatic incorporation of these modified nucleotides to DNA was successfully performed using Phusion polymerase for primer extension. One of the dNTPs (dCTP bearing cholic acid) was also efficient for PCR amplification.
Keywords: Nucleic Acid Denaturation; nukleosidy; Bile Acids and Salts; denaturace nukleových kyselin; DNA; Thermococcaceae; DNA-Directed DNA Polymerase; Nucleosides; nukleotidy; DNA-dependentní DNA-polymerasy; žlučové kyseliny a soli; Nucleotides